On exploring managerial challenges through grounded theory method - Wilczewska, Martyna (MATEC web of conferences, 2025)
A reliable theory base is a cornerstone of any scientific discipline. In the case of applied disciplines such as management, particular emphasis is placed on developing theories that are both scientifically rigorous and empirically relevant. To that end, middle-range and local theories are often proposed within the discipline, providing contextually reliable theoretical explanations of management phenomena. This article examines a set of theories generated through the grounded theory method that address various aspects of different managerial challenges. Based on an analysis of relevant literature sample, the study identifies the most common areas of management explored and the theoretical contributions proposed as a result. In doing so, it offers a comprehensive overview of middle-range theories that engage with real-life management phenomena. At the same time, it demonstrates the merits of using grounded theory method to develop valuable theoretical contributions that can positively influence the advancement of the management discipline and inform management practice.